CPIA Africa, June 2013 : Assessing Africa's Policies and Institutions - World Bank (Washington, DC, 2014)
This report is the second in a series of annual reports describing the progress African countries are making on strengthening the quality of policies and institutions that underpin development. It presents Country Policy and Institutional Assessment (CPIA) scores for the 39 African countries that are eligible for support from the International Development Association (IDA). The development literature identifies the components of the CPIA as being broadly relevant for sustaining growth and reducing poverty. The data provide some support for this association. All country groups exhibit similar patterns across the four CPIA clusters. The gap in scores between the macroeconomic management cluster and the governance cluster is just as pronounced for fragile as for non-fragile states. In contrast, the gap between the economic management cluster and the social policies and structural policies clusters is small. Overall, the macroeconomic policy stance in Sub-Saharan Africa was supportive of growth, with monetary policy focused on managing inflation and fiscal policy focused on pro-poor spending and infrastructure development. Inflation declined in 2012, thanks to a moderation in food and fuel prices and prudent monetary policy. However, an expansive fiscal policy translated into a weakening of fiscal balances. Debt levels also edged up, although they remained moderate. As the policy areas in this cluster are closely related, there tends to be co-movement in the scores for monetary and fiscal policy.